Green Chemistry — Present and Future Issues - Dhiman, Vijayant (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
The basis of green chemistry is frequently considered as a response to the need to reduce the damage of the environment by man-made materials and the processes used to produce them. A quick view of green chemistry issues in the past decade demonstrates many methodologies that protect human health and the environment in an economically beneficial manner. This article presents selected examples of the implementation of green chemistry principles in everyday life in industry, the laboratory and in education. A brief history of green chemistry and future challenges are also mentioned.